Supply Chain Challenges of Personal Protective Equipment, and Methods of Mitigation Amidst COVID-19 Pandemic: A Qualitative Study from Sri Lanka, a Developing Country in South East Asia - Talagala, Ishanka Ayeshwari (Archives of Clinical and Biomedical Research, 2025)
Background: Personal Protective equipment (PPE) are essential for healthcare workers to prevent disease spread. With COVID-19 pandemic, the PPE supply chain was adversely affected. This case-study describes the PPE supply chain challenges and mitigation measures during COVID-19 pandemic in Sri Lanka. Methods: In-depth interviews were conducted among 14 randomly selected officials, who were directly involved with PPE procurement to Ministry of Health Sri Lanka, at the Medical Supplies Division, State Ministry of Production Supply and Regulation of Pharmaceuticals and State Pharmaceutical Corporation. Study sample was collected until data saturation. A semi-structured interviewer guide was used. Thematic analysis was done. Results: Study revealed that the preparation for an un-interrupted PPE supply prior to pandemic hitting the country was unsatisfactory. High cost; unavailability of certified suppliers; unavailability of PPE globally and locally; lack of raw materials; quality failure; delays in procurement procedure; increased demand and its dynamicity; and lack of funds challenged the PPE supply chain. Intergovernmental negotiations; encouraging local production and purchasing from local suppliers; issuing guidelines for PPE usage; and obtaining support from development partners/INGOs were the mitigation strategies that were undertaken. Conclusions: Sri Lanka, as a country with limited resources, has faced several PPE supply chain challenges during the pandemic. Policy makers should undertake measures to improve the readiness prior to similar disasters in the future. Encouraging local PPE production, establishing quality assurance mechanisms, developing relevant guidelines and improving staff capacity on procurement process are recommended to face disasters of such caliber in the future.